The Therapeutic Effect of Zuogui Wan in Gestational Diabetes Mellitus Rats - Yuwei Wang; Qianjin Feng; Xin Niu; Xinshe Liu; Kaixia Xu; Xiangzhu Yang; Huifeng Wang; Qiuju Li (Journal of Analytical Methods in Chemistry)
In this experiment, we established an animal model of gestational diabetes mellitus rats using streptozotocin. Using the rat model of GDM, the pregnant rats in 1-19d were divided into three groups: (1) Zuogui Wan gestational diabetes mellitus group (group I, n=12), (2) gestational diabetes mellitus rats as the control group (group II, n=11), and (3) rats of normal pregnancy group (group III, n=11). Compared with gestational diabetes mellitus rats as the control group, Zuogui Wan can change the indexes of fasting blood glucose, body weight, total cholesterol, insulin, and metabolism cage index significantly in Zuogui Wan gestational diabetes mellitus group. We can conclude that Zuogui Wan has the therapeutic effect on gestational diabetes mellitus.